Syringe Administration of Epinephrine by Emergency Medical Technicians for Anaphylaxis. (4th May 2018) - Latimer, Andrew J.; Husain, Sofia; Nolan, Jonathan; Doreswamy, Vinod; Rea, Thomas D.; Sayre, Michael R.; Eisenberg, Mickey S.
Abstract: Objective : In recent years, the costs of epinephrine autoinjectors (EAIs) in the United States have risen substantially. King County Emergency Medical Services implemented the "Check and Inject" program to replace EAIs by teaching emergency medical technicians (EMTs) to manually aspirate epinephrine from a single-use 1 mg/mL epinephrine vial using a needle and syringe followed by prehospital intramuscular administration of the correct adult or pediatric dose of epinephrine for anaphylaxis or serious allergic reaction. Treatment was guided by an EMT protocol that required a trigger and symptoms. We sought to determine if the "Check and Inject" program was safely implemented by EMTs treating presumed prehospital anaphylaxis or serious allergic reaction.Methods : We conducted a prospective investigation of all cases treated as part of the "Check and Inject" program from July 2014 through December 2016 in suburban King County, Washington, and January 2016 through December 2016 within the city of Seattle. All cases were prospectively collected using a custom quality improvement data form completed by the first responding EMTs. Two physicians completed a structured review of each EMS medical record to determine if the EMTs followed the Check and Inject protocol and determine if epinephrine was clinically-indicated based on physician review.Results : Of the 411 cases eligible for analysis, EMTs followed the protocol appropriately in 367 (89.3%) cases. In the remaining 44 (10.7%) cases, the EMS incident report form failed to document either a clear inciting allergic trigger or an appropriate symptom from the protocol list. Physician review determined that epinephrine was clinically indicated in 36 of the 44 cases. Among the remaining 8 cases (1.9%) that did not meet protocol criteria and were not clinically-indicated based on physician review, none had a documented adverse reaction to the epinephrine.Conclusion : We observed that EMTs successfully implemented the manual "Check and Inject" program for severe allergic reactions and anaphylaxis in a manner that typically agreed with physician review and without any overt identified safety issues.